Occurrence of plasmids in multi metal and drug resistant gram negative bacteria isolated From hospital wastewater - MANZAR ALAM,; MOHD IMRAN,; MOHD ARIF, (International Journal of Pharma and Bio Sciences, 2017)
Plasmids are extra-chromosomal pieces of DNA, which are capable of replicating independently of the genome, and are particularly significant in extend of antibiotic resistance genes. Occurrence of plasmids in multiple metal and drug resistant Gram negative bacteria was observed. Most of the Gram negative bacterial isolates were found containing plasmid and showed different numbers, size and molecular weight. Various plasmids of different sizes were observed in Gram negative species. E. coli isolates contained plasmids with size ranging from 44.0kb to 58.0kb, while Enterobacter aerogens isolates (ENT 52 and ENT 154, 167) contained plasmids of size ranging from 43.0 to 57.0kb. Four E. coli isolates (EC 171, EC 172, EC 173 and EC 181) contained common size of plasmid of 46.5 kb while two Enterobacter aerogens isolates (ENT 154 and ENT 167) contained common size of plasmid of 57.0kb. Proteus vulgaris isolates contained plasmid of size ranging from 42.5 to 57.0kb, whereas in Pseudomonas aeruginosa isolates plasmid size ranged from 35.0 to 48.0kb. The findings suggested that plasmids are highly ubiquitous and predominant in most heavy metal and antibiotic resistant bacteria. The hospital wastewater containing bacteria having higher antibiotic and heavy metal resistance levels presents a potential public health risk, as well as the threat of transferring the antibiotic and metal resistance plasmid to bacterial populations in the environment.